UPAYA MENUMBUH-KEMBANGKAN MINAT GEMAR BEROLAHRAGA PADA KELOMPOK USIA REMAJA - Sri Mawarti (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2006)
This paper intends to reveal the effort to grow teenager interest on sport. We include juniorhigh school student as the teen age, a transition age. At this age level, they hunger to searchfor self-identity. At this point, the interest on sport not all of it came from internal interest, thusrequiring a way to grow their interest.Sport that gives fun, joy, and unity can be use as a weapon to encourage teens to do sportactivities. Body contact sports can be use as a channel in search for identity. These sportgive a prestige when the teen capable acquired a satisfactory achievement, thus this sportcan be use as a model to encourage sport activities especially to boys.Keyword: Interest, sports, Teenage.